Evading the Lockdown: Animal Metaphors and Dehumanization in Virtual Space. (2nd January 2022) - Ho, Janet
ABSTRACT: COVID-19 has posed a serious threat to more than 200 countries, causing over one million deaths worldwide (as of December 2020) and leading to lockdowns that are unprecedented in modern times. Given the physical restrictions, social media platforms have become crucial for people to maintain contact and share ideas during the pandemic. In this paper, I examine the discursive representations of evaders of the Wuhan lockdown. Specifically, I investigate how social media users employed animal metaphors to portray the identities of people who fled Wuhan during this time. More than 250 posts with over 15, 000 comments were collected from the Chinese microblogging site Weibo; data were thematically analyzed, and metaphors were identified. The results demonstrated that various kinds of animal metaphors were used to discredit the evaders and to highlight their objectionable behavior and moral standards. The use of violent expressions associated with animal metaphors also revealed the issue of dehumanization vis-à-vis all the residents in Wuhan, which has various theoretical and ideological implications. The findings suggest that, while dehumanizing the evaders by likening their health status to that of infected animals, the users unconsciously revealed the evaders' helplessness and inability to control their situation, reflecting ideological ambivalence.